PROGRAMACIÓN AVANZADA CON DERIVE®. APLICACIONES AL ÁLGEBRA LINEAL - Castro Chadid, Iván; Facultad de Ciencias Pontificia Universidad Javeriana, Bogotá Universidad Nacional De Colombia, Bogotá (2013)
In this Article, the Author builds up a set of procedures that allow the solution of six usual problems of great importance in Linear Algebra and its applications. Taking advantages of DERIVE® computational Algebra programs and sorne ideas offered by sorne demonstrative methods, the Author reachs a perfect balance between synthesis and efficiency